Revealing the Faraday depth structure of radio galaxy NGC 612 with broad-band radio polarimetric observations. Issue 2 (5th February 2018) - Kaczmarek, J F; Purcell, C R; Gaensler, B M; Sun, X; O'Sullivan, S P; McClure-Griffiths, N M
Abstract: We present full-polarization, broad-band observations of the radio galaxy NGC 612 (PKS B0131-637) from 1.3 to 3.1 GHz using the Australia Telescope Compact Array. The relatively large angular scale of the radio galaxy makes it a good candidate with which to investigate the polarization mechanisms responsible for the observed Faraday depth structure. By fitting complex polarization models to the polarized spectrum of each pixel, we find that a single polarization component can adequately describe the observed signal for the majority of the radio galaxy. While we cannot definitively rule out internal Faraday rotation, we argue that the bulk of the Faraday rotation is taking place in a thin skin that girts the polarized emission. Using minimum energy estimates, we find an implied total magnetic field strength of 4.2 μG.